Academic –community collaboration in innovative rural community-based health promotion programmes in Sabah: 11 years retrospective study (2007-2018) - Naing Oo Tha; Mohd Yusof Ibrahim; Patricia Sator; Rajesh Kumar Muniandy; D Kamarudin D Mudin; Mohammad Saffree Jeffree (The Ijaseat Journal, 2019)
Traditional health promotion programmes are not effective or sufficient to reduce disease prevalence and in outreach remote communities as innovative health promotion programmes using new paradigm Community Based participatory Research model (CBPR). Universiti Malaysia Sabah has annual health promotion programme using CBPR since 2007. It was sustainable for 11 years and still ongoing every year. Concept of health promotion, planning, need assessment and implementation of health promotion were introduced to young medical students every year in a co-curriculum module by series of weekend lectures. Groups of year 1 medical students were supervised by supervisors in each group and distributed to various villages of remote rural areas in end of year 1 in their semester break. Students’ groups plan their health promotion programmes before going to selected villages by consulting coordinator and stakeholder of programmes such as District health officer, health clinic staff and head of villages. Coordination and planning for accommodation, transportation and budget allocation for Health promotion materials as well as daily expenses are arranged for 2 weeks period with academic-community- stakeholder partnership. Objective of this study is to highlight the impact of academic –community partnership in rural Sabah population by remote rural health promotion programmes by medical students. Methods – The retrospective evaluation for barriers and critical success factors in partnership of planning phases in annual health promotion programmes was done for the period of 2008-2018. Data were analyzed by using student group presentations, supervisor individual assessment, group reports and coordinator records. FindingsResults shows for the descriptive summary of programmes coverage in Sabah with 40 various areas in Sabah and 80 remote rural villages in 11 years period. There are no barriers in partnership such as unequal power, conflict of resources and cultural clashes. In planning phase, the strengths of the programmes are strong leadership from university, theory knowledge and supervision, stakeholder participation and partnership, financial support from university, time to time supervision and coordination of academicians and transportation provided by university. There are critical success factors with long and trusted history of collaboration with Sabah State Health department and district health offices, mutual respect understanding and trust of each stakeholder: academician, students, community leaders and district health authorities and staff with flexible structure and adaptability in partnership in 11 years period producing successful and attainable goals with shared vision to improve rural community health. Innovative remote rural health promotion programmes are successfully being implemented with strong academic community partnership by adopting community based participatory research model from all stakeholders with sharing goals and vision which is increasing health and wellbeing of community by taking action and social norms and values changed for better healthy communities in Sabah.